2019
DOI: 10.1002/jor.24239
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro injection of osteoporotic cadaveric femurs with a triphasic calcium‐based implant confers immediate biomechanical integrity

Abstract: Current pharmaceutical therapies can reduce hip fractures by up to 50%, but compliance to treatment is low and therapies take up to 18 months to reduce risk. Thus, alternative or complementary approaches to reduce the risk of hip fracture are needed. The AGN1 local osteo‐enhancement procedure (LOEP) is one such alternative approach, as it is designed to locally replace bone lost due to osteoporosis and provide immediate biomechanical benefit. This in vitro study evaluated the initial biomechanical impact of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 48 publications
(104 reference statements)
1
25
1
Order By: Relevance
“…The consistency and magnitude of the increases in femoral strength combined with the sustained nature of the femoral strength gains through 5-7 years indicate that AGN1 LOEP likely provides a long-term benefit to osteoporotic subjects. In addition to the likely long-term benefit, a prior study in human cadaveric femurs demonstrated that AGN1 implantation also leads to an immediate increase in femoral strength [18]. Although the sample size does not allow for a statistical assessment of fracture reduction, increased aBMD and femoral strength via FEA correlates with bone strength and fracture risk reduction [19,20,22,23], suggesting that AGN1 LOEP has the potential to reduce hip fracture risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The consistency and magnitude of the increases in femoral strength combined with the sustained nature of the femoral strength gains through 5-7 years indicate that AGN1 LOEP likely provides a long-term benefit to osteoporotic subjects. In addition to the likely long-term benefit, a prior study in human cadaveric femurs demonstrated that AGN1 implantation also leads to an immediate increase in femoral strength [18]. Although the sample size does not allow for a statistical assessment of fracture reduction, increased aBMD and femoral strength via FEA correlates with bone strength and fracture risk reduction [19,20,22,23], suggesting that AGN1 LOEP has the potential to reduce hip fracture risk.…”
Section: Discussionmentioning
confidence: 99%
“…Real-world hip fracture prevention with drug therapy is further limited due to under-diagnosis of osteoporosis, limited prescription of pharmaceutical therapies to osteoporotic patients, delayed onset of effectiveness of these therapies, and an incomplete 30 to 51% hip fracture risk reduction [11,24,26,28]. In contrast, AGN1 LOEP provides immediate [18] and as noted above, long-term protection, and compliance is guaranteed as the treatment is a one-time procedure. Moreover, the AGN1 LOEP treatment response was observed in all subjects whether or not they were taking anti-resorptive drugs, demonstrating the feasibility of using AGN1 LOEP in patients on systemic osteoporosis therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simple protocol for collecting and storing the skin from dead donors makes possible the successive skin transplants in patients with extensive burns, decreasing their mortality or in the therapy of hard-to-heal wounds ( Sachkov et al, 2018 ), including lower limbs ulcers not susceptible to other treatment ( Mosti et al, 2020 ). Additionally, postmortem collected bones, due to keeping their mechanical properties after the death, served as research material in studies evaluating the effect of local bone reinforcement by injecting a three-phase calcium-based implant, the novel osteoporosis treatment ( Stroncek et al, 2019 ). Postmortem collected bone fragments can be frozen up to eight times without losing their morphological and biomechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…A local osteo-enhancement procedure utilizing resorbable, triphasic calcium sulfate/calcium phosphate injectable implant material is under clinical investigation as a means of preventing osteoporotic hip fractures. The implant material increased the fracture strength of cadaveric osteoporotic femurs [9]. This approach to strengthening at risk osteoporotic vertebra has not been previously studied.…”
Section: Introductionmentioning
confidence: 99%